Hand washing behavior among school children in Sekolah Kebangsaan Sultan Abdullah, Kuantan, Pahang - Al-Araji, Laith Issa Yassin; Umar , Nur Syazana; Wan Su, Kamaruzaman (2011)
Absenteeism school children are usually related to respiratory and gastrointestinal disease as children are more susceptible to be infected with dangerous bacteria and viruses. Therefore, hand washing is the single most important measure to prevent the spread of infection. School children should be taught and stressed about the importance of hand-washing. A cross-sectional study was held in Sekolah Kebangsaan Sultan Abdullah, Kuantan, Pahang, The participants were school pupils aged 10 to 12 years old and data was obtained from questionnaires and observation to evaluate their hand washing techniques. The objective of this study was to know their hand washing behaviors and techniques as well as to understand the conditions that affect hand-washing behaviors in school. It can be concluded that 86 of the students (49.7%) had proper hand washing behavior. Age, individual intention, perceive control and attitude were found to have association with hand washing behavior. In addition, it was found that 40.8% of the respondents were having correct hand washing techniques. Overall, the results of this study will help in promoting better hand washing behavior and techniques among school children particularly as it is the best way to prevent from infections which can lead to increase number of morbidity and mortality.